Efeito da incorporação do chamote em argilas para a produção de cerâmicas utilitárias no Distrito de Icoaraci, Belém - PA - GOMES, Gabriel da Silva (2019)
Aiming to obtain refractory pans in the ceramic pole of Icoaraci, this work had the effect of improving the incorporation of singe for a high value of 400 ºC for the possible cooking of foods. The chamote was obtained from the tailings of ceramic artifacts, such as burners, such as vases, plates, others; The waste was manually ground, obtaining a granulometry similar to that used by Bragança artisans, where the refractory pieces with the addition of chamote are traditionally produced and even exported. This is the use of the quantum of heavy metal and organic organic organic organic piggies; through X-ray diffraction were the minerals in total and in the clay fraction. In addition, the clay titre was added in 5, 10, 15 and 20%, by preparing clay samples for each of the mixtures to be burned in an artisan kiln of the Icoaraci. In these pieces with chamote also were eliminated in some technological conditions. In addition, they were analyzed in Scanning Electron Microscope (SEM), for the study of microtextures, and by X-ray Detector by Dispersive Energy (EDS). All samples of clays have the same compositions that encompass the characteristics of the ingredients and are made in Brazilian ceramic products. With the technology of the tests, pointed out the composition of 15% of chamote would be more suitable, due to the linearity of linear retraction, loss of mass to the fire, water absorption and apparent porosity were smaller than the other compositions and their ratio of work was not changed. However, there was also a reduction in resistance. This behavior is attributed to the greater presence of quartz, a fact that was proven in studies that supported this research.